Class Performance, A Step toward An Authentic Assessment in Teaching English to Young Learners - Fatimah, Nur (Universitas Ahmad Dahlan, 2014)
AbstractCommunicative language teaching leads language learners to be able to use the language in real-life or real-life like situations. Through the learning activities, the learners are facilitated to use the language for communicative performance in the target language. Class performance is one of the activities enabling the learners to use their knowledge and to apply their skills in the demanded communication event(s). The performance provides a situation where learners can develop different skills. During the performance tasks, the teacher can observe, monitor and at the same time, the teacher can get ideas to prepare an authentic assessment. To deal with these pedagogical issues in teaching English to young learners (TEYL), the writer of this paper discusses the benefits of performance, the practice of class performance in TEYL and some insights for a performance and authentic assessment.